Faktor – Faktor yang Mempengaruhi Kejadian Demam Berdarah Dengue (DBD) Di Kelurahan Pekat Kecamatan Sumbawa Kabupaten Sumbawa - Lina Safitri; Abdul Hamid; Nur Arifatus Sholihah; Siti Amanah Bentan Sakinah (LPPM STIKES Griya Husada Sumbawa, 2021)
Dengue Hemorrhagic Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus belonging to the Arthropod-Borne Virus. Study aims to determine the factors that influence the incidence of DHF in Pekat District, Sumbawa Regency, Sumbawa Regency. Research method is quantitative research withresearch design cross-sectional. The sample in this study were 93 respondents in Kel. Concentrated District. Sumbawa Regency Sumbawa Regency was carried out in May - June 2021. The results of the univariate analysis were obtained from the incidence of DHF who suffered from DHF as many as 22 respondents (23.7%), good knowledge as many as 54 respondents (58.1%), good PSN as many as 56 respondents ( 60.2%), the habit of hanging clothes 28 respondents (30.1%), the use of mosquito repellent as many as 47 respondents (50.5%). From the results of thetest, chi square it is known that there is no effect between knowledge and the incidence of DHF value OR count (0.367) < OR table (3.841) and p count (0.544) > p table (0.05), there is an effect between PSN and DHF incidence OR value count (9,700) > OR table (3,841) and p value (0,002) < p table (0,05), there is no influence between habit of hanging clothes with DHF incidence X² count (1,948) < X² table (3,841) and p count ( 0.163) > p table (0.05), there is an effect between the use of mosquito repellent and the incidence of DHF OR count (12.069) > OR table (3.841 ) and p count (0.001) < p table (0.05)